(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2024)
The importance of the English language cannot be overstated in today’s globalized world. English language learning is crucial in today’s world for several reasons. It serves as a bridge that connects people from different cultures and backgrounds.We can say that learning English language is key for us today. Because language learning is important for us opens many doors for our future life.